Photodynamic antimicrobial chemotherapy on streptococcus mutans using curcumin and toluidine blue activated by a novel LED device - Paschoal, Marco Aurélio Benini [UNESP]; Lin, Meng; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Duarte, Simone (Springer Nature, 2015)
Photodynamic antimicrobial chemotherapy (PACT) is an antimicrobial approach that uses photosensitizers (PS) in combination with light sources at specific wavelengths aiming the production of reactive oxygen species. The long illumination time necessary to active PS is a challenge in PACT. Thus, this study investigated the antimicrobial effect of a novel single source of light-emitting diode (LED) light that covers the entire spectrum of visible light beyond interchangeable probes at high power intensity. Blue and red LED probes were used into different exposure times to active different concentrations of curcumin (C) and toluidine blue (T) on planktonic suspensions of Streptococcus mutans UA 159 (S. mutans). S. mutans were standardized and submitted to (1) PACT treatment at three concentrations of C and T exposure at three radiant exposures of a blue LED (BL) (C+BL+) and a red LED (RL) (T+RL+), (2) C (C+BL−) or T alone (T+RL−), (3) both LED lights (C−BL+ and T−RL+), and (4) neither PS nor LED illumination (control group: C−BL− and T−RL−). Aliquots of the suspensions were diluted and cultured on blood agar plates. The number of colony-forming units was calculated after 48 h. The groups submitted to PACT presented a lethal photokilling rate to all PS concentrations at tested dosimetries. The comparison to control group when PS and LED lights used alone demonstrated no decrease in the number of viable bacterial counts. The novel LED device in combination with curcumin and toluidine blue promoted an effective photoinactivation of S. mutans suspensions at ultrashort light illumination times.
Keywords: Caries; Curcumin; Photodynamic therapy; Bacteria